Psychometric Properties of the Oncology Module of the KINDL Scale: First Results. (March 2015) - Ergin, Dilek; Eser, Erhan; Kantar, Mehmet; Ekti Genç, Rabia
Purpose . The objective of this study was to assess the reliability and validity of the Oncology module of the generic KINDL scale (having 24 items with 6 domains). Methods . The psychometric properties of the KINDL Oncology module were evaluated from the aspect of internal consistency, reliability, and construct validity on an inpatient sample of 103 Turkish children (mean age 10.0 ± 4.01 years) who had various oncological disorders. Results . The KINDL Oncology module (24 items) showed acceptable α coefficients ranging from .57 (physical well-being) to .87 (treatment) for each domain. In confirmatory factor analysis of the original 4-domain structure, Root Mean Square Error of Approximation was found as .086, and Comparative Fit Index was .87. Good known groups results supported the construct validity of the instrument. Correlations between the domains of the mother KINDL and the domains of its oncology module were significantly high, indicating a satisfactory convergent validity. Conclusion . The Turkish version of the KINDL Oncology module showed good reliability and questionable validity in this study. However, further research on other language versions of the module is needed for its global use.